Occupational Carpal Tunnel Syndrome: a scoping review of causes, mechanisms, diagnosis, and intervention strategies - Rotaru-Zavaleanu, Alexandra-Daniela; Lungulescu, Cristian Virgil; Bunescu, Marius Gabriel; Vasile, Ramona Constantina; Gheorman, Victor; Gresita, Andrei; Dinescu, Venera Cristina (Frontiers in Public Health, 2024)
Carpal Tunnel Syndrome (CTS) has traditionally been viewed as a specialized medical condition. However, its escalating prevalence among professionals across a multitude of industries has sparked substantial interest in recent years. This review aims to delve into CTS as an occupational disease, focusing on its epidemiological patterns, risk factors, symptoms, and management options, particularly emphasizing its relevance in professional environments. The complex interaction of anatomical, biomechanical, and pathophysiological factors that contribute to the development of CTS in different work settings underlines the critical role of ergonomic measures, prompt clinical identification, and tailored treatment plans in reducing its effects. Nevertheless, the challenges presented by existing research, including diverse methodologies and definitions, highlight the need for more unified protocols to thoroughly understand and tackle this issue. There's a pressing demand for more in-depth research into the epidemiology of CTS, its injury mechanisms, and the potential role of targeted medicine. Moreover, recognizing CTS's wider ramifications beyond personal health is essential. The economic burden associated with CTS-related healthcare costs, productivity losses, and compensation claims can significantly impact both businesses and the broader society. Therefore, initiatives aimed at preventing CTS through workplace interventions, education, and early intervention programs not only benefit the affected individuals but also contribute to the overall well-being of the workforce and economic productivity. By fostering a collaborative approach among healthcare professionals, employers, policymakers, and other stakeholders, we can strive towards creating safer and healthier work environments while effectively managing the challenges posed by CTS in occupational settings.